Allozyme and restriction fragment length polymorphism analyses confirm Entomophaga maimaiga responsible for 1989 epizootics in North American gypsy moth populations. - Hajek, A E (1990)
In 1989, populations of North American gypsy moth, Lymantria dispar, in seven contiguous northeastern states were severely reduced by a fungal pathogen. Based on morphology, development, and pathology, this organism appeared to be Entomophaga maimaiga. We have now used allozyme and restriction fragment length polymorphism analyses to confirm this identification. Previously, this mycopathogen had been reported only from gypsy moth populations in Japan. During 1989, E. maimaiga occurred only in areas that had been initially defoliated by gypsy moth >10 years ago. E. maimaiga caused 60-88% mortality in late instar larvae on research sites in central Massachusetts.